2021
DOI: 10.1038/s41467-021-23737-1
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-oxidase like catalytic mechanism of noble metal nanozymes

Abstract: Au nanoparticles (NPs) have been found to be excellent glucose oxidase mimics, while the catalytic processes have rarely been studied. Here, we reveal that the process of glucose oxidation catalyzed by Au NPs is as the same as that of natural glucose oxidase, namely, a two-step reaction including the dehydrogenation of glucose and the subsequent reduction of O2 to H2O2 by two electrons. Pt, Pd, Ru, Rh, and Ir NPs can also catalyze the dehydrogenation of glucose, except that O2 is preferably reduced to H2O. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
167
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(174 citation statements)
references
References 45 publications
(44 reference statements)
7
167
0
Order By: Relevance
“…Besides, the power density indicated that the performance of ACB@algae biofuel cell was 2.1 times and 2.39 times higher than that of ACB or BOD biofuel cells in the O 2 saturated solution, respectively. It should be noted that excessive O 2 may diffuse to the anode to hinder the glucose oxidation reaction by accepting the electrons from the Au NPs 54 . While for the ACB@algae biofuel cell, the strategy of O 2 ‐generated in situ leads to low O 2 concentration in electrolyte.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the power density indicated that the performance of ACB@algae biofuel cell was 2.1 times and 2.39 times higher than that of ACB or BOD biofuel cells in the O 2 saturated solution, respectively. It should be noted that excessive O 2 may diffuse to the anode to hinder the glucose oxidation reaction by accepting the electrons from the Au NPs 54 . While for the ACB@algae biofuel cell, the strategy of O 2 ‐generated in situ leads to low O 2 concentration in electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that excessive O 2 may diffuse to the anode to hinder the glucose oxidation reaction by accepting the electrons from the Au NPs. 54 While for the ACB@algae biofuel cell, the strategy of O 2 -generated in situ leads to low O 2 concentration in electrolyte. These results showed that the electrocatalytic ORR performance with the ACB@algae cathode is not only superior to pure BOD biofuel cell fed by O 2 bubbling, but also very competitive with previously reported BFC using native microalgal cells (Table S1).…”
Section: The Acb@algae As a Cathode In A Membrane-less Bfc Cellmentioning
confidence: 99%
“…Enzymatic properties of gold nanoparticles (Au NPs) have widespread uses in biomedical applications [ 110 ]. Many studies have reported that Au NPs exhibited multiple-enzymes mimicking abilities such as peroxidase-mimetic activity and glucose oxidase (GOD) activity [ 111 113 ]. The GOD-like activity of Au nanoparticles can deplete the glucose and generate H 2 O 2 , which could effectively consume glucose nutrients and inducing cell starving in tumor tissues.…”
Section: Gold-based Nanozymesmentioning
confidence: 99%
“…For the GOx-mediated oxidation of one glucose molecule, two electrons are formed by the production of one gluconolactone and one H 2 O 2 . Based on the high research and application significance, diverse types of nanomaterials comprising noble metals and metal oxides have been studied as GOx-mimicking nanozymes [ 35 , 36 , 37 , 38 , 39 ]. Among them, gold nanoparticles (Au NPs) have been a focus of investigation, and interestingly, their glucose oxidation mechanism was proposed to be the same as that of natural GOx [ 35 ], which is highly affected by morphological features, including size, and reaction environments, including temperature, pH, and reaction time [ 37 ] ( Figure 2 ).…”
Section: Synthetic Strategies and Catalytic Characteristics Of Nanozymes To Replace Natural Enzymes In Glucose Biofuel Cellsmentioning
confidence: 99%
“…Based on the high research and application significance, diverse types of nanomaterials comprising noble metals and metal oxides have been studied as GOx-mimicking nanozymes [ 35 , 36 , 37 , 38 , 39 ]. Among them, gold nanoparticles (Au NPs) have been a focus of investigation, and interestingly, their glucose oxidation mechanism was proposed to be the same as that of natural GOx [ 35 ], which is highly affected by morphological features, including size, and reaction environments, including temperature, pH, and reaction time [ 37 ] ( Figure 2 ). Interestingly, the GOx-like activity of Au NPs was further improved by utilizing a molecularly imprinted polymer functionalized on their surface, resulting in a 270-fold higher catalytic activity than that of bare Au NPs [ 39 ].…”
Section: Synthetic Strategies and Catalytic Characteristics Of Nanozymes To Replace Natural Enzymes In Glucose Biofuel Cellsmentioning
confidence: 99%